2022
DOI: 10.1097/hcr.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of the First Pritikin Outpatient Intensive Cardiac Rehabilitation Program

Abstract: Pritikin Intensive Cardiac Rehab 449C ardiac rehabilitation (CR) is a medically supervised treatment program designed to promote optimal recovery after a cardiac event or procedure and to reduce the risk for future cardiac events in patients with cardiovascular disease (CVD). 1,2 Exercise is the central focus of CR, with additional instruction on healthy dietary patterns and lifestyle behaviors that impact cardiovascular risk. Cardiac diagnoses that are approved by the Centers for Medicare & Medicaid Services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…9 More recent studies have demonstrated that patients in ICR had better postrehabilitation scores on fitness, physical function, diet quality, and greater decreases in body mass index compared with those in CR. 17,18 Although these benefits could explain, at least in part, the improved survival seen with ICR over CR, future studies are needed to explore these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 More recent studies have demonstrated that patients in ICR had better postrehabilitation scores on fitness, physical function, diet quality, and greater decreases in body mass index compared with those in CR. 17,18 Although these benefits could explain, at least in part, the improved survival seen with ICR over CR, future studies are needed to explore these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller, nonrandomized, retrospective, and prospective studies have shown differences between ICR and CR. 9,17 For example, a small observational study conducted before CMS’s approval of outpatient ICR demonstrated reduced hospitalization rates and trends towards reduced Medicare costs and reduced all-cause mortality with intensive lifestyle modification programs that were the forebears of current ICR programs. 9 More recent studies have demonstrated that patients in ICR had better postrehabilitation scores on fitness, physical function, diet quality, and greater decreases in body mass index compared with those in CR.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle modification to prevent coronary artery disease (CAD) includes enhancing exercise and physical activity, improving dietary habits and emotional stability, smoking cessation, etc., to manage CAD risks [1,2] The secondary prevention named as cardiac rehabilitation has traditionally been hospital-based with conventional regimens, but it has some barriers that make it difficult for patients to enroll and adhere to the program, despite its benefits and effectiveness [3]. For these reasons, emerging approaches, such as home-based rehabilitation and intensive cardiac rehabilitation, have been introduced to complement the weaknesses of conventional methodologies [2][3][4][5][6]. Those approaches could be applied to primary prevention, too.…”
Section: Introductionmentioning
confidence: 99%